Simultaneous Calculation of Flow and Diffusion Sensitivity in Steady-State Free Precession Imaging - Gudbjartsson, Hákon (1995)
In this paper the authors quantitatively evaluate the combined effect of both flow and diffusion in steady-state free precession (SSFP) imaging. A partition analysis (PA) is used to derive a fourth order approximation (in E(2)) of the signal in an echo SSFP sequence. The authors also introduce a novel very fast simulation technique, based on a circular convolution, which accurately accounts for both flow and diffusion. A 2D SSFP-echo sequence was implemented to obtain experimental data from a phantom containing three different solutions. Excellent agreement between the theory and the experimental data was found. Then by using the simulation algorithm and experimental measurements of in vivo brain motion, the authors estimated the artifacts to be expected in SSFP diffusion imaging of the brain and found them to be comparable with those of pulsed gradient spin echo. Finally, the authors point out the equivalence between the flow sensitivity of SSFP and RF spoiling commonly used in fast imaging.